2015
DOI: 10.1016/j.molcel.2014.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-Dependent Lysosomal Membrane Protein Sorting and Degradation

Abstract: As an essential organelle in the cell, the lysosome is responsible for digestion and recycling of intracellular components, storage of nutrients, and pH homeostasis. The lysosome is enclosed by a special membrane to maintain its integrity, and nutrients are transported across the membrane by numerous transporters. Despite their importance in maintaining nutrient homeostasis and regulating signaling pathways, little is known about how lysosomal membrane protein lifetimes are regulated. We identified a yeast vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
144
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(159 citation statements)
references
References 51 publications
(54 reference statements)
13
144
2
Order By: Relevance
“…We co-expressed Ypq1-GFP and myc-Ub in doa4 Δ cells. Doa4 is a major deubiquitinase of the endomembrane system, and its deletion stabilizes ubiquitinated forms of Ypq1 (Amerik et al, 2000; Li et al, 2015b). We immunoprecipitated Ypq1-GFP before and after lysine withdrawal, and probed the precipitates for myc-Ub.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We co-expressed Ypq1-GFP and myc-Ub in doa4 Δ cells. Doa4 is a major deubiquitinase of the endomembrane system, and its deletion stabilizes ubiquitinated forms of Ypq1 (Amerik et al, 2000; Li et al, 2015b). We immunoprecipitated Ypq1-GFP before and after lysine withdrawal, and probed the precipitates for myc-Ub.…”
Section: Resultsmentioning
confidence: 99%
“…Rsp5 is recruited to the vacuole membrane by Ssh4, a PY-motif containing type-I transmembrane protein. After ubiquitination, Ypq1 is sorted into the vacuole lumen for degradation (Li et al, 2015b). We also reported that the zinc transporter Cot1 is ubiquitinated by Tul1, a RING-type E3 ligase, and is sorted into the vacuole lumen for degradation upon the depletion of zinc (Li et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] Originally ESCRT complexes were identified to regulate multi-vesicular body formation and lysosomal sorting. 5 However several ESCRT proteins were demonstrated also to be required for cytokinesis. 6 Thus it was proposed that the recruitment of various ESCRT complex members, such as CHMP4, to the midbody, lead to a formation of filaments that mediate the final abscission step 7 ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the putative uncharacterised protein (gi|749901469), predicted protein (gi|170094730) and Hsp20/alpha crystalline family (gi|227085992) belong to heat shock proteins and function as molecular chaperone, which participate in the folding of nascent polypeptide chains and the transmembrane transport of proteins (Beckmann, Mizzen, & Welch, 1990;Fu, 2014). Predicted protein (gi|403418016) is the ubiquitin-dependent protein which is believed to have the protein catabolic function (Li, Rong, Chuang, Peng, & Emr, 2015). With the addition of coenzyme Q0, the expression level of the heat shock proteins were increased while that of ubiquitin-dependent protein was decreased.…”
Section: Effect Of Coenzyme Q0mentioning
confidence: 99%